Investigation of infection of intestinal parasites Entamoeba histolytica and Giardia lamblia among patients which attending of the Health Centers of Gharraf City / Thi- Qar province - Shaymaa Z. Al-Rumaidh; Bassad A. AL-Aboody; Ahmed Salman Abdul-Al hasan (University of Thi-Qar Journal of Science, 2019)
The intestinal parasites of Entamoeba hstolytica and Giardia lamblia are among the major causes of diarrhea throughout the world.The current study was conducted from October 2015 to February 2016 to investigate the spread of intestinal parasites Entamoeba histolytica and Giardia lamblia for patients who have been referred to the Gharraf Model Center and the Main Graff center , which suffer from intestinal disorders. The study included 488 stool samples for patients of different ages and both sexes (males and females). The number of samples required for examination was 228 and 46.72% compared with 260 negative samples for examination and 53.27%. The positive results were 202 for  Entamoeba histolytica parasites by 5, 88% compared with 20 and 8.7% of the Giardia lamblia parasite and 2.6 % for Entamoeba hstolytica and Giardia lamblia.The study showed no significant differences between males and females. The highest rates of parasitic infection in the largest of the 15-year age group, which reached 49.12%. The highest incidence of the city population was 65.75% compared with the Rusticate population 34.21%.